Dialogic Reading Method in Improving The Understanding of Emotion on Children 4-6 Years Old - Nurvinkania, Ayu Aulia; Salim, Rose Mini Agoes (FKIP Universitas Lampung, 2024)
Dialogic Reading Method in Improving The Understanding of Emotion on Children 4-6 Years Old. Objectives: The purpose of this study was to examine how effectively the dialogic reading approach helped children aged 4 to 6 understand emotions. Methods: A sample of 25 participants was used in a pretest-posttest design. Pons and Harris (2004) evaluated emotional comprehension using the Test of Emotional Comprehension (TEC). Children's pretest, posttest, and one-week follow-up posttest findings were included in the research data. The data was analyzed using the Wilcoxon signed-rank test. Findings: after the dialogic reading intervention, there was a significant improvement in emotional understanding scores. Compared to the pretest, the average posttest score (5.68) was higher. Additionally, the average score on the posttest after a week was 6.52. This study revealed a variety of remarkable conclusions about the dialogic reading intervention. Certain aspects of the CROWD reading strategies Complete questions, Repeat questions, Open-ended questions, WH questions, Distancing questions, and unique prompts showed greater levels of interest than others. For example, WH and open-ended questions were very engaging and encouraged children to elaborate on their experiences and provide answers. Children also gave thoughtful answers that differed from the set responses. These answers point to a more nuanced comprehension of emotions and raise the possibility that the TEC is not fully capable of handling a range of responses. Social connections and interpersonal processes shape the children's experiences and statements. Conclusion: The dialogic reading intervention is effective in enhancing emotional understanding in 4- to 6-year-old children. The findings of this study can serve as a valuable reference for educators and parents in developing intervention programs to support children's emotional development. Keywords: dialogic reading, emotion comprehension, emotion understanding, early childhood.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024145